A Failed Challenge to Validity Generalization: Addressing a Fundamental Misunderstanding of the Nature of VG. Issue 3 (30th August 2017) - Schmidt, Frank L.; Viswesvaran, Chockalingam; Ones, Deniz S.; Le, Huy
Abstract : The lengthy and complex focal article by Tett, Hundley, and Christiansen (2017 ) is based on a fundamental misunderstanding of the nature of validity generalization (VG): It is based on the assumption that what is generalized in VG is the estimated value of mean rho ( $\bar{ρ}$ ). This erroneous assumption is stated repeatedly throughout the article. A conclusion of validity generalization does not imply that $\bar{ρ}$ is identical across all situations. If VG is present, most, if not all, validities in the validity distribution are positive and useful even if there is some variation in that distribution. What is generalized is the entire distribution of rho ( $\bar{ρ}$ ), not just the estimated $\bar{ρ}$ or any other specific value of validity included in the distribution. This distribution is described by its mean ( $\bar{ρ}$ ) and standard deviation ( SDρ ). A helpful concept based on these parameters (assuming ρ is normally distributed) is the credibility interval, which reflects the range where most of the values of ρ can be found. The lower end of the 80% credibility interval (the 90% credibility value, CV = $\bar{ρ}$ – 1.28 × SDρ ) is used to facilitate understanding of this distribution by indicating the statistical "worst case" for validity, for practitioners using VG. Validity has an estimated 90% chance of lying above this value. This concept has long been recognized in the literature (see Hunter & Hunter, 1984, for an example; see also Schmidt, Law, Hunter, Rothstein, Pearlman, & McDaniel, 1993, and hundreds of VG articles that have appeared in the literature over the past 40 years since the invention of psychometric meta-analysis as a means of examining VG [Schmidt & Hunter, 1977 ]). The $\bar{ρ}$ is the value in the distribution with the highest likelihood of occurring (although often by only a small amount), but it is the whole distribution that is generalized. Tett et al. (2017 ) state that some meta-analysis articles claim that they are generalizing only $\bar{ρ}$ . If true, this is inappropriate. Because $\bar{ρ}$ has the highest likelihood in the ρ distribution, discussion often focuses on that value as a matter of convenience, but $\bar{ρ}$ is not what is generalized in VG. What is generalized is the conclusion that there is validity throughout the credibility interval. The false assumption that it is $\bar{ρ}$ and not the ρ distribution as a whole that is generalized in VG is the basis for the Tett et al. article and is its Achilles heel. In this commentary, we examine the target article's basic arguments and point out errors and omissions that led Tett et al. to falsely conclude that VG is a "myth."